Conceptualising transformative undergraduate experiences: A phenomenographic exploration of students' personal projects. (12th September 2016) - Ashwin, Paul; Abbas, Andrea; McLean, Monica
Abstract : Existing ways of understanding the transformative potential of students' undergraduate experiences either focus solely on the formal educational elements of these experiences or present an overly static picture of students' intentions in engaging in higher education. In this article we argue that the notion of 'personal project' offers a more flexible way of understanding what students are trying to gain from being at university. Based on a phenomenographic analysis of interviews with 31 students over the three years of their degrees, we examine how sociology students' accounts of their personal projects develop over the three years of their degree programmes and how these relate to their accounts of their integration into their institutions and the development of their intellectual engagement with their discipline. We argue that students' accounts of their personal projects are relatively stable over the course of their degrees but do not appear to shape the development of their intellectual engagement with their degree programme. What appears to be more significant is whether or not students understand their time at university as an educational experience. Based on this, we argue that the transformative elements of an undergraduate education lie in students developing their personal projects and intellectual engagement through the educational context that is offered at university.